COMMON PROBLEMS AND THEIR SOLUTIONS FOR LEARNING THE ENGLISH LANGUAGE - Djalolov, Furqat (Журнал иностранных языков и лингвистики, 2021)
This article deals withbasic problems and using suitable methods for teaching English.